(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Undergraduate college students have been identified as at-risk population for development of suicidal ideation and depression. Student nurses are among those who experience depression and anxiety due to stressful life events. The stressful situations encountered by student nurses are multifaceted. Thus, this study explored the level of depression and suicidal ideation of BSN students and the effect of gender and year level. The need to explore these two salient factors was prompted by the need to promote and to improve school of nursing services, student safety, and decrease cases of depression and suicidal ideation among students. The study utilized a descriptive design. There were 326 student nurses who participated in the study. The questionnaire which was used for this study was based on 2 standardized self – report questionnaire. The findings showed that most of the students experienced mild to severe depression. Most of the students however, do not have suicidal ideation behavior, but almost one third of the students have a high risk for suicidal ideation behavior. Furthermore, the findings showed that gender and year level have no significant effect on the level of depression among BSN Students. Gender and year level have no significant effects in the level of suicidal ideation among student nurses. These findings can help guide the development of a school-based, prevention and promotion mental health program.